Switching administration of anti‐PD‐1 and anti‐PD‐L1 antibodies as immune checkpoint inhibitor rechallenge in individuals with advanced non‐small cell lung cancer: Case series and literature review. Issue 7 (18th May 2020) - Kitagawa, Shingo; Hakozaki, Taiki; Kitadai, Rui; Hosomi, Yukio
Abstract : Background: Based on several phase III studies, immune checkpoint inhibitors (ICIs) are essential and promising drugs for the treatment of non‐small cell lung cancer (NSCLC). However, in patients previously treated with ICI, the efficacy and safety of rechallenging the same or another type of ICI inhibitor remain unclear. Moreover, clinical data about the efficacy of switching the administration of anti‐programmed death‐1 (PD‐1) antibodies (e.g. nivolumab, pembrolizumab) and anti‐programmed death‐ligand 1 (PD‐L1) antibodies (e.g. atezolizumab) as ICI rechallenge are limited. Thus, the current study aimed to evaluate the efficacy and safety of such treatment strategy in NSCLC patients. Methods: We retrospectively reviewed the medical records of 17 patients with advanced or recurrent NSCLC who received both anti‐PD‐1 and anti‐PD‐L1 antibodies during their clinical courses. Results: Among the 17 patients, one (5.9%) and nine (52.9%) achieved partial response and stable disease, respectively, after ICI rechallenge. The median progression‐free survival of ICI rechallenge in these patients was 4.0 (range: 0.4–8.0) months, and the median overall survival from the start of the initial ICI was 31.0 (range: 7.6–46.8) months. Of the 10 patients who developed immune‐related adverse events (irAEs) during the first ICI treatment, five presented with these events after the readministration of ICI. Among them, four experienced relapsed irAEs and two patients had pneumonitis, which is a grade 3 or higher irAE. Almost all irAEs during the rechallenge treatment were manageable. Conclusions: Switching the administration of anti‐PD‐1 and anti‐PD‐L1 antibodies as ICI rechallenge could be a treatment option for some NSCLC patients. Key points: Significant findings of the study: In this study, switching the administration of anti‐PD‐1 and anti‐PD‐L1 antibodies as ICI rechallenge could be an effective and safe treatment option for some patients with advanced or recurrent NSCLC. What this study adds: Switching the administration of ICI may increase the efficacy of readministration. However, the mechanism is unknown. Thus, further accumulation of cases is required, and extensive investigations must be conducted to elucidate the mechanism and benefits of such treatment.